Enhancing Fluency in Speaking through Task-Based Teaching and Learning - Quynh, Nguyen Hoa Phuong (Journal of Ecohumanism, 2025)
The paper’s primary goal is to evaluate the effectiveness of the TBLT, which stands for Task-Based Language Teaching methodology, in English language education and acquisition among eleventh and fourteenth grades. The project is implemented in a standard classroom at the VMG English center. In this case study, the students completed focused reasoning-gap and problem-solving projects over the duration of eight weeks, with all their presentations, conversations, and arguments being recorded and graded to provide them with constructive feedback. The study’s findings would demonstrate the TBLT application’s efficiency in English-speaking instruction. In other words, the EFL learners’ capacity for fluent communication, together with their grammatical accuracy, variety of vocabulary, conversation’s abundant information, and rate of speech, are all significantly improved. The significance of the study’s results for future research will be examined and discussed in the context of practical teaching and learning.